Examining the Relationship Between Fear of Failure and Career Indecision Among Final-Year University Students in Bekasi City - Muhammad Farid Alifianto; Yuarini Wahyu Pertiwi; Wahyu Aulizalsini Alurmei (Socrates: Journal of Education, Philosophy and Psychology, 2026)
Career anxiety constitutes one of the most prevalent psychological challenges encountered by final-year undergraduate students as they navigate the critical transition from higher education to the labor market. This condition has the potential to impair the process of career decision-making, particularly among individuals characterized by elevated levels of fear of failure. The present study aimed to investigate the relationship between fear of failure and career indecision among final-year undergraduate students in Bekasi City. A quantitative approach with a correlational design was employed. Participants were recruited through purposive sampling, yielding a final sample of 100 students who met the predetermined inclusion criteria. Data were collected using an adapted version of the Performance Failure Appraisal Inventory (PFAI; Conroy, 2001) to assess fear of failure, and an adapted version of the Career Decision Difficulties Questionnaire (CDDQ; Gati et al., 1996) to measure career indecision. Data were analyzed using Pearson Product-Moment correlation. Results revealed a significant positive relationship between fear of failure and career indecision (r = .494; p < .001). The majority of participants exhibited high levels of fear of failure and moderate levels of career indecision. These findings indicate that higher fear of failure is associated with greater difficulty in making career decisions. The study contributes to the literature on career psychology and offers an empirical basis for developing targeted psychological interventions to support students in their career decision-making process.